Why Extracellular Vesicles Are Attractive Vehicles for RNA-Based Therapies? - Farah Aqel; Kristin Schneider; Denise Hartung; Kathrin Schwarz; Olga Shatnyeva (SynBio)
Extracellular Vesicles (EVs) are a focus of intense research worldwide, with many groups exploring their potential for both diagnostic and therapeutic applications. Researchers have characterized EVs into various subtypes, modified common surface markers, and developed diverse isolation and purification techniques. Beyond their diagnostic potential, EVs are being engineered as delivery vehicles for various molecules and therapeutics. RNA therapeutics have the potential to be a transformative solution for patients suffering from chronic and genetic disorders and generally targeting undruggable targets. Despite the success of many RNA therapeutics in both in vivo studies and clinical trials, a significant challenge remains in effectively delivering these therapies to the target cells. Many research groups have adopted the use of lipid nanoparticles (LNPs) and other nanocarriers to encapsulate RNA therapeutics, aiming to deliver them as stably as possible to ensure optimal bioavailability and efficacy. While LNPs have proven successful as delivery vehicles, their use is not without drawbacks, such as accumulation within the body. EVs could be a potential solution to many of the problems around LNPs and other nanocarriers.